2011
DOI: 10.2174/156652411795976565
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and Diabetes-Associated Pathologies

Abstract: Osteoprotegerin (OPG) is a member of the tumour necrosis factor receptor superfamily of cytokines which, in spite of being initially described as a strong anti-resorptive factor, has lately been considered as a possible link between bone and vascular disease. In the last few years, several studies have evidenced its close relationship with the development of diabetes. In this review, we analyse the role of OPG in diabetic patients and its links with the most relevant associated diseases such as atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 146 publications
(272 reference statements)
1
19
0
Order By: Relevance
“…Altered circulating osteoprotegerin levels are linked with metabolic disease, however whether osteoprotegerin may be implicated in obesity remains an open question, given the conflicting data between published studies [12]. Osteoprotegerin also appears to play a role in diabetes outcomes, such that osteoprotegerin levels are higher in T2D [26], and can predict mortality [27]. Here, we found that circulating osteoprotegerin levels are significantly reduced 2 and 12 weeks after bariatric surgery.…”
Section: Discussionmentioning
confidence: 58%
“…Altered circulating osteoprotegerin levels are linked with metabolic disease, however whether osteoprotegerin may be implicated in obesity remains an open question, given the conflicting data between published studies [12]. Osteoprotegerin also appears to play a role in diabetes outcomes, such that osteoprotegerin levels are higher in T2D [26], and can predict mortality [27]. Here, we found that circulating osteoprotegerin levels are significantly reduced 2 and 12 weeks after bariatric surgery.…”
Section: Discussionmentioning
confidence: 58%
“…Fetuin, another factor that prevents vascular calcification, was recently reported to be present in kidney-derived exosomes [5]. The presence of OPG in circulating microvesicles should be explored since plasma OPG is associated with increased cardiovascular risk [51], [52].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that abdominal obesity, IR, and NAFLD are associated with decreased osteoprotegerin levels [36,37].…”
Section: Low Bone Mineral Density (Osteoporosis/osteomalacia)mentioning
confidence: 99%